2003
DOI: 10.1002/anie.200352102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Oligonucleotides Containing the C4′‐Oxidized Abasic Site Produced by Bleomycin and Other DNA Damaging Agents

Abstract: Exposure of DNA to oxidative stress produces strand scission and a variety of damaged nucleotides, which can be mutagenic and/or cytotoxic. The determination of the effects of specific lesions on nucleic acid structure, stability, and their interaction with polymerase and repair enzymes provide a chemical basis for the biological effects of DNA damage. [1,2]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…40 DNA lesions also cleave faster in single stranded material. 41, 42 In contrast, cleavage from 5,6-dihydrouridin-6-yl radical ( 2 ) ( k Cleave ) was less than 100 s −1 in either single or double stranded RNA and strand scission was faster in the latter substrate. 10 The dependency of k Cleave on secondary structure indicated that C2'-radical ( 4 ) cleavage could not be the rate limiting step.…”
Section: Resultsmentioning
confidence: 99%
“…40 DNA lesions also cleave faster in single stranded material. 41, 42 In contrast, cleavage from 5,6-dihydrouridin-6-yl radical ( 2 ) ( k Cleave ) was less than 100 s −1 in either single or double stranded RNA and strand scission was faster in the latter substrate. 10 The dependency of k Cleave on secondary structure indicated that C2'-radical ( 4 ) cleavage could not be the rate limiting step.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we and other groups have developed methods for independently producing C4-AP from stable precursors in chemically synthesized oligonucleotides. 4,2831 In this study, C4-AP was generated on an as needed basis from the photolabile precursor ( 5 ), which was incorporated into oligonucleotides from phosphoramidite 4 during solid-phase DNA synthesis (Scheme 1). 4 The general sequence in 1 is part of a restriction fragment from pBR322, which possesses a hot-spot for cleavage by bleomycin.…”
Section: Resultsmentioning
confidence: 99%
“…General Approach for Synthesizing Oligonucleotides Containing DOB Using the synthesis of the respective C4-AP phosphoramidite as a guide, we viewed 11 (Scheme 6) as a key synthetic intermediate. 11 Stereocontrolled synthesis of 11 was initially pursued by attempted nucleophilic substitution of the protected glycerol derivatives (14, 15) (Scheme 5). The stereochemistry was set using the asymmetric dihydroxylation of the pmethoxybenzoate of allyl alcohol (12).…”
mentioning
confidence: 99%